Contrasts and classtalk: A critical discourse analysis of welfare-to-work program managers. (September 2014) - Turgeon, Brianna; Taylor, Tiffany; Niehaus, Laura M
Historically, discourse about welfare in the United States has changed from a language of 'need' to a culture of 'dependency'. Adopting 'dependency' as a frame to construct the public opinion of welfare, workers help maintain the current punitive welfare state. In this study, we use critical discourse analysis to examine how county program managers in Ohio, USA ( N = 69) use several discursive techniques to legitimate their identities as good workers while neutralizing negative connotations associated with administering welfare policy. Further, we find managers use discursive techniques of contrast to heighten boundaries between three pairings: (1) 'generational' and 'situational' clients, (2) clients and non-clients, and (3) welfare workers and clients. Managers engage in 'classtalk' in their contrasts in a way that blames the poor through contrasts with others with 'middle-class values'.